Burden of esophageal cancer in global, regional and national regions from 1990 to 2021 and its projection until 2050: results from the GBD study 2021 - Zhang, Chengcheng; Chen, Linzhi; Xiu, Yuqi; Zhang, Hongling; Zhang, Yuejuan; Ying, Wenjuan (Frontiers in Oncology, 2025)
BackgroundEsophageal cancer (EC) is a major global health issue characterized by high morbidity and mortality rates, with a notably low five-year survival rate. Comprehensive analyses of the global burden of EC remain limited and outdated, despite its global significance. This study aimed to systematically assess the global burden and trends of esophageal cancer across diverse populations.MethodsData on the burden of EC were collected from the Global Burden of Disease (GBD) 2021 study, including estimates of incidence, mortality, and disability-adjusted life years (DALYs), as well as risk factors, spanning 204 countries and territories. Age-standardized rates (ASRs) were calculated to allow comparisons across populations. The study further explored the relationship between EC burden and socioeconomic development by utilizing the Socio-demographic Index (SDI), aggregating data by regions. The Bayesian age-period-cohort model was applied to project future trends until 2050.ResultsIn 2021, there were 576,529 new esophageal cancer cases, with an age-standardized incidence rate (ASIR) of 6.65 per 100,000, reflecting a 24.87% decrease since 1990. The global number of deaths reached 538,602, with an age-standardized death rate (ASDR) of 6.25 per 100,000, representing a 30.67% decline. DALYs totaled 12,999,264, corresponding to an estimated annual percentage change (EAPC) of a 1.73% decrease in the age-standardized DALYs rate. East Asia accounted for nearly two-thirds of global EC cases and deaths, while Central Sub-Saharan Africa recorded the highest ASIR and ASDR. Central Asia experienced the largest reductions, whereas Western Sub-Saharan Africa showed increasing trends. Middle-SDI countries, such as Malawi and Lesotho, had disproportionately high burdens, while high-SDI countries, including Tunisia and Kuwait, had lower burdens. Males had higher incidence and mortality rates across all age groups. By 2050, the ASIR is projected to decrease to 6.17 per 100,000, and the ASDR to 5.23 per 100,000, though the absolute number of cases and deaths is expected to rise.ConclusionsThe global burden of EC remains significant, with ongoing challenges in regions such as Africa and East Asia. These findings highlight the need for sustained and targeted prevention efforts, particularly in high-risk populations, to address the increasing absolute number of cases and deaths.